The Mboi collection of Atma Jaya Catholic University in Jakarta - Wieringa, Edwin P. (UI Scholars Hub, 2019)
Since 2018 the private collection of Ben Mboi (1935-2015), who is best known as Governor of East Nusa Tenggara – NTT – from 1978 to 1988, has been part of the Library of Atma Jaya Catholic University in Jakarta, where it is publicly accessible under the name of Ben Mboi Research Library. The collection totals 22,890 items; the majority of the books are written in English, Indonesian, and Dutch. After briefy introducing the life and work of Ben Mboi, this article frst discusses the phenomenon of private libraries in Indonesia, making it clear that Mboi’s collection is highly unusual. The main part of the paper explores the question as to what is specifcally “Mboian” about the library and what it tells us about his mindset. Mboi’s library functioned as a collection for a working mind and the essay focuses on his books dealing with good governance, which increasingly occupied Mboi’s mind after he entered the world of politics. Special attention is paid to reader’s marks and annotations: Mboi read his books from a decidedly Indonesian perspective. This is particularly evident in the case of Dutch books written by Dutch academics on contemporary Dutch society, which Mboi studied intensively in order to refect upon the situation in post-Suharto Indonesia. Mboi’s own political thinking, which advocated elitism and organicist statecraft, conformed to mainstream ideological discourse in the New Order, but is still de rigueur in post-Suharto Indonesia, showing a remarkable overlap with colonial ideas about leadership in the period of Dutch high imperialism.